Transformasi Genetik Tanaman Kentang cv. Atlantik Dengan Mengintroduksikan Gen Hordothionin untuk Mendapatkan Ketahanan terhadap Penyakit Bakteri - Nurhasanah, ,; Wattimena, G. A.; Purwito, Agus; Wiendi, Ni Made Armini; Suharsono, , (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2003)
Hordothionins are small anti-bacteria proteins present in barley endosperm, To reveal the potential of this proteins for engineering bacterial disease resistance into potato, a semi-synthetic hordothionin gene construct was introduced in potato cv. Atlantic via Agrobacterium tumefaciens strain LBA 4404, under the control of a cauliflower mosaic virus (CaMV) 358 promotor. The in vitro grown stem (internodus) was used in this research. After 6 weeks in regeneration medium and 2 weeks in rooting medium there were 22 regenerated plants that were screened in kanamycine containing medium. PCR analysis using spesific primer from CaMV 358 promotor showed the presence of amplified T-DNA in 4 transgenic lines from 22 putative transgenic plants were tested, The in vitro toxicity against Ralstonia solanacearum tested from transgenic lines showed variation in resistance level, There were only 2 of the transgenic lines were tolerant, while one of them was moderate tolerant even one of them was susceptible. Key words: Potato, Hordothionin gene, Disease resistance